2013
DOI: 10.1038/jid.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin-D3-3-Bromoacetate Regulates AKT/mTOR Signaling Cascades: A Therapeutic Agent for Psoriasis

Abstract: The efficacy of 1α,25-dihydroxyvitamin D3 (Vit-D) limits its topical use despite its profound effects on cellular differentiation, proliferation, and immunomodulation. Therefore, in search for a more effective analog of Vit-D, in this study we have evaluated the antiproliferative and proapoptotic effects of 1α,25-dihydroxyvitamin D3-3-bromoacetate (BE). Proliferation and apoptosis studies in normal human epidermal keratinocytes (NHEKs) were conducted by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…428, a validation study with three different RhE models -EpiDerm™, EpiSkin™ and SkinEthic™ -indicated their general suitability for in vitro absorption studies, both in infinite and finite dose experiments (Schafer-Korting et al, 2008). Though the permeability rate determined using RhEs seems to exceed that found using ex Mitra et al, 2013;Eves et al, 2003;Li et al, 2011;Tjabringa et al, 2008).…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 61%
“…428, a validation study with three different RhE models -EpiDerm™, EpiSkin™ and SkinEthic™ -indicated their general suitability for in vitro absorption studies, both in infinite and finite dose experiments (Schafer-Korting et al, 2008). Though the permeability rate determined using RhEs seems to exceed that found using ex Mitra et al, 2013;Eves et al, 2003;Li et al, 2011;Tjabringa et al, 2008).…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 61%
“…Interestingly, IL-22 is not only able to activate mTOR signaling but also induces the expression of mTOR mRNA [31]. Strong activation of mTORC1 in the basal compartment seems to be at least partially involved in proliferative control.…”
Section: Discussionmentioning
confidence: 99%
“…Calcipotriol was found to suppress Th17-induced psoriasin and koebnerisin in psoriatic skin [84]. In an epidermal reconstructed model of psoriasis, Datta Mitra et al [85] showed that 1α,25-dihydroxyvitamin D 3 -3-bromoacetate, a vitamin D analog, has a more potent antiproliferative action compared to 1,25(OH) 2 D 3 . He showed that bromoacetate reverses the psoriasiform changes induced by IL-22 in the reconstructed epidermal model by inhibiting the expression of AKT1, MTOR, chemokines (IL-8 and RANTES) and psoriasin (S100A7).…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%